Penerapan SAW Method Untuk Menentukan Produk Unggulan Berdasarkan Penjualan Nisa Collection - Dini Selfidayanti; William Ramadhan; Sudarmin (Jurnal Algoritma, 2026)
This study aims to apply the Simple Additive Weighting (SAW) method in a web-based Decision Support System (DSS) to determine the leading products in the Nisa Collection. The problem faced is that the determination of leading products is still subjective and only considers one sales indicator. This study analyzes 10 product alternatives based on four criteria, namely sales volume (0.40), transaction frequency (0.15), stock turnover (0.20), and price (0.25). The calculation process is carried out through the formation of a decision matrix, normalization of benefits and costs, and calculation of preference values. The results show that alternative A7 (Men's T-shirts) obtained the highest preference value of 1.00, followed by A1 and A2 with a value of 0.92. The sensitivity test shows that the top ranking remains stable against weight changes, confirming the consistency of the method. The scientific contribution of this research lies in the comprehensive application of SAW in the context of MSME retail based on quantitative sales data with decision stability analysis, thus providing an objective, measurable, and transparent product evaluation model compared to previous manual approaches.